Incident-angle-controlled semitransparent colored perovskite solar cells with improved efficiency exploiting a multilayer dielectric mirror. Issue 37 (18th September 2017) - Lee, Kyu-Tae; Jang, Ji-Yun; Park, Sang Jin; Ok, Song Ah; Park, Hui Joon
Abstract : See-through colored perovskite solar cells that exploit a dielectric mirror are demonstrated. The dielectric mirror strongly reflects a wide range of visible light back to a photoactive layer for efficient light-harvesting, yielding 10.12% power conversion efficiency, with iridescent semitransparent colors. Abstract : See-through perovskite solar cells with high efficiency and iridescent colors are demonstrated by employing a multilayer dielectric mirror. A certain amount of visible light is used for wide color gamut semitransparent color generation, which can be easily tuned by changing an angle of incidence, and a wide range of visible light is efficiently reflected back toward a photoactive layer of the perovskite solar cells by the dielectric mirror for highly efficient light-harvesting performance, thus achieving 10.12% power conversion efficiency. We also rigorously examine how the number of pairs in the multilayer dielectric mirror affects optical properties of the colored semitransparent perovskite solar cells. The described approach can open the door to a large number of applications such as building-integrated photovoltaics, self-powered wearable electronics and power-generating color filters for energy-efficient display systems.